The Methodological Quality of Case Series Published Early vs. Late in the Course of a Pandemic: A Meta-Epidemiologic Study - Alsawaf, Yahya; Firwana, Mohammed; Nayfeh, Tarek; Seisa, Mohamed O.; Alsibai, Reem A.; Abbas, Alzhraa S.; Lees, Elizabeth H.; Zhu, Ye; Wolf, Michael E.; Vanichkachorn, Greg; Hegazi, Moustafa; Prokop, Larry J.; Murad, M. Hassan; Saadi, Samer (Avicenna Journal of Medicine, 2025)
Introduction Case reports and series are critical to guide initial decision-making in a pandemic, but may have lower rigor because of the need to publish them quickly. This meta-epidemiologic study compares the methodological quality of case series that described the acute coronavirus disease 2019 (COVID-19) pandemic in 2020 versus those that described long-haul cases.Methods We conducted a systematic review in multiple databases for long-haul case series and reports. We identified early cases of acute COVID-19 synthesized in published systematic reviews. We evaluated the methodological quality by pairs of independent reviewers using a tool dedicated for appraising case series.Results We included 239 original case series (81 published in the first year of the pandemic and 158 published later describing long-haul COVID). The methodological quality of both groups of case series was very good (80–100% of series satisfying quality items) except for two items, the selection approach of cases included in the series and ruling out other causes that can explain the main finding described in the series. The appraisal tool demonstrated high agreement and reliability between reviewers.Conclusion The methodological quality of modern case series is high, except for two quality items that represent an area for potential for improvement for authors of case series describing future pandemics.
Keywords: methodological quality; risk of bias; meta-epidemiological research; case series; case reports